Cross-Modal Iconism at Tully’s Coffee Japan - Ezra Toback (Semiotic Review)
Tully’s Coffee Japan seeks to differentiate itself from competitors in the chain-cafe service industry. It does this in part through the semiotic figuration of two modernist discourses of distinction: culinary-craft authenticity and egalitarian sociability. This figuration is grounded in the corporate strategy of cross-modal iconism, or the production of a perceived equivalence between elements of heterogeneous sign systems. In Tully’s cafes, cross-modal iconism is instantiated through forms of linguistic labor that lend distinction to the company and its workers, products, and customers. On the one hand, employees vocalize set Italianate phrases in entextualized performances scripted by the corporation. The use of these phrases leverages iconic and indexical values ideologically invested in Italian to position Tully’s employees closer to an imagined, authenticating origin located in western Europe. On the other hand, Tully’s refers to employees with the loanword “ferō,” a term hitched to an image of egalitarian sociability thought to characterize democratic European cafe culture. Both the Italianate calls and “ferō” draw upon two historical strains that run through Japan’s cafe modernity: elitism and popularism. These strains reemerge at Tully’s today in the contradiction between the hierarchical social relations implied by the Italianate calls and the equalized social relations implied by “ferō.”